Health factor in soft drink consumption, German example - Lőrinczi, Krisztián (Applied Studies in Agribusiness and Commerce, 2009)
Consumer lifestyle and health are relevant factors to understanding consumption preferences.The number of lifestyle diseases has dramatically increased worldwide. The main cause for these diseases is the change in lifestyle; including a lack of attention to physical activity and good nutrition. Health and lifestyle are important factors by purchase decision process. In accordance with these, I examine the consumer behaviour toward soft drinks with special regards to healthy lifestyle and the state of health. My examinations can be considered mainly as a qualitative research among German students, which can serve as a basis for further analyses and research, however, the conclusions and experience gained from it are worthy of consideration. I differentiated five categories: ice tea, carbonated soft drinks, fruit juices, mineral waters, sport and energy drinks and studied the consumer behaviour toward them. The study focuses on the consumption of these and the factors influencing their purchase with special regards to lifestyle.